Study the in vitro effect of alcoholic extract of Prunus aremasia kernels, Methotreaxte, amygdalin and the combination between them on Hela cancer cell line - kafi, Lubna A. (Iraqi Journal of Cancer and Medical Genetics, 2015)
This study was done to evaluation the cytotoxicity of each apricot kernels ethanolic extract at concentration (100-500) µg/ ml, amygdalin and methotreaxat at concentration (0.1-1000) µg/ml, (plant extract plus methotreaxat) and (amygdalin plus methotreaxat) at half the original concentration for each one on Hela (human cervical cancer cell line) in vitro . A mixtures of (extract plus Methotreaxte) and (amygdalin plus Methotreaxte) was used together to evaluated its cytotoxicity on cancer cell line for indentify about the possibility of synergistic effect between them. The results shows the cytotoxicity of (plant extract and methotreaxat) on Hela cancer cell line was same as the cytotoxicity of plant extract alone and more than the cytotoxicity of Methotreaxte alone, while the cytotoxicity of (amygdalin and methotreaxat) on Hela cancer cell line is similar to the cytotoxicity of amygdalin alone and more than the cytotoxicity of Methotreaxte alone.